Preparation method of tear-resistant tent fabric

By using high-performance fibers such as ultra-high molecular weight polyethylene on the base fabric of the tent fabric and setting a wear-resistant layer composed of materials such as polyurethane emulsion on the surface, the problem of easy tear and wear resistance is solved, achieving higher tear and wear resistance, and extending the service life of the tent.

CN119824689APending Publication Date: 2025-04-15NANTONG ABLE OUTDOOR PROD COMPANY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411789917.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing tent fabrics are prone to tear during use, especially when rubbing against rough ground or being damaged by sand and gravel in windy and sandy weather, making it difficult to maintain the integrity of the tent.

Method used

Ultra-high molecular weight polyethylene, cationically modified polyester and flame retardant acrylic are used as the base cloth layer, and the wear-resistant layer and waterproof layer are successively set on the surface of the base cloth layer. The wear-resistant layer consists of polyurethane emulsion, wear-resistant filler, wetting agent, defoaming agent, thickening agent and leveling agent, and nano-alumina and polytetrafluoroethylene wax are the main components of the wear-resistant filler.

Benefits of technology

It effectively improves the tear resistance and wear resistance of the tent fabric, extends the service life of the tent, and improves the waterproof and windproof effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005175073180000091
    Figure BDA0005175073180000091
Patent Text Reader

Abstract

The invention relates to the technical field of fabrics, and particularly discloses a preparation method of an anti-tear tent fabric. According to the preparation method of the tear-resistant tent fabric, the tent fabric comprises a base cloth layer, a waterproof layer and a wear-resistant layer, the waterproof layer and the wear-resistant layer are sequentially arranged on the surface of the base cloth layer, and the base cloth layer is prepared from ultra-high molecular weight polyethylene, cation modified polyester and flame-retardant acrylic fibers; the wear-resistant layer comprises the following raw materials in parts by weight: 30-40 parts of polyurethane emulsion; 5-10 parts of a wear-resistant filler; 0.3-1 part of a wetting agent; 0.2 to 0.8 part of a defoaming agent; 0.5 to 2 parts of a thickening agent; and 0.1 to 0.5 part of a leveling agent. The tear-resistant tent fabric can be used for outdoor tents, and has the advantages of excellent and lasting tear resistance, wear resistance and water resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of fabrics, and in particular to a method for preparing tear-resistant tent fabrics. Background Art

[0002] When camping outdoors, tents are essential equipment. Tents must have multiple outdoor functions such as sunshade, ventilation, windproof, rainproof, and warmth. Outdoor tents must adapt to various weather environments, so there are higher requirements for tents produced by enterprises. Existing tents need to add multiple coatings on the base fabric of the tent to enhance the function of the tent itself, so that the produced tents are more practical and can have effective sunshade, ventilation, windproof, rainproof, and warmth functions. In particular, tents are more likely to rub against rough ground during use, and in windy and sandy weather, sand and stones can easily damage the tent, so the tent also needs to have better tear resistance to maintain the integrity of the tent. Summary of the invention

[0003] In order to obtain a tent that is windproof, rainproof and tear-resistant, the present application provides a method for preparing tear-resistant tent fabric, which adopts the following technical solution:

[0004] A method for preparing tear-resistant tent fabric, the tent fabric comprising a base fabric layer, a waterproof layer and a wear-resistant layer sequentially arranged on the surface of the base fabric layer, the base fabric layer is made of ultra-high molecular weight polyethylene, cationic modified polyester and flame-retardant acrylic fiber; the wear-resistant layer comprises the following raw materials in parts by weight:

[0005] 30-40 parts of polyurethane emulsion;

[0006] 5-10 parts of wear-resistant filler;

[0007] Wetting agent 0.3-1 part;

[0008] Defoaming agent 0.2-0.8 parts;

[0009] Thickener 0.5-2 parts;

[0010] 0.1-0.5 parts of leveling agent.

[0011] By adopting the above technical scheme, the technical scheme of this application preferably adopts ultra-high molecular weight polyethylene, cationic modified polyester and flame-retardant acrylic as the base fabric layer. Ultra-high molecular weight polyethylene fiber is a high-performance fiber recognized in the world today, with the advantages of light weight, high strength, high modulus, light resistance, friction resistance, cutting resistance, flex resistance, acid and alkali resistance, and resistance to general organic solvents. The base fabric prepared by ultra-high molecular weight polyethylene staple fiber / cationic modified polyester / flame-retardant acrylic fiber is light in weight, easy to carry, and has extremely high tear strength. It also has the functions of waterproof and breathable, flame retardant, UV protection, mildew resistance, aging resistance, and chemical corrosion resistance. The unique puncture and cut resistance of ultra-high molecular weight polyethylene fiber can be fully utilized, thereby effectively improving the easy tearing effect of the tent fabric.

[0012] The present application preferably adopts the method of sequentially setting a wear-resistant layer and a waterproof layer on the surface of the base fabric. The setting of the wear-resistant layer can reduce the possibility of friction damage between the tent fabric and the ground. The setting of the waterproof layer can improve the waterproof effect of the tent fabric and reduce the possibility of damage to the tent caused by rainwater erosion of the tent fabric.

[0013] It is preferred to use polyurethane emulsion and wear-resistant filler to form a wear-resistant coating. The polyurethane emulsion itself has good mechanical properties, wear resistance and oil resistance. The introduction of wear-resistant filler can further increase the wear resistance and mechanical strength of the wear-resistant coating, so that the tent fabric has excellent wear resistance and service life.

[0014] Optionally, the mass ratio of the ultra-high molecular weight polyethylene, the cationic modified polyester and the flame-retardant acrylic fiber is 60-70:20-30:10-20.

[0015] By adopting the above technical solution, the mass ratio of ultra-high molecular weight polyethylene, cationic modified polyester and flame-retardant acrylic is optimized. At an appropriate mass ratio, the tent fabric can be given excellent tear resistance and flame retardant properties, thereby extending the service life of the tent.

[0016] Optionally, the density of the ultra-high molecular weight polyethylene is 0.920-0.964 g / cm 2 .

[0017] Optionally, the wear-resistant filler includes nano-alumina and polytetrafluoroethylene wax.

[0018] By adopting the above technical scheme, nano alumina is filled in the wear-resistant layer as a hard aggregate to form a supporting skeleton in the wear-resistant layer, which is beneficial to improve the hardness and strength of the wear-resistant layer. The wear-resistant filler is protruded during the friction process, which further protects the wear-resistant layer. Especially after the initial stage of wear, the filler particles protrude more and more, and the wear occurs selectively on the filler surface, and the wear of the entire wear-resistant layer is stable.

[0019] Polytetrafluoroethylene wax is filled in the gaps of polymer materials. When the surfaces slide relative to each other, the polytetrafluoroethylene macromolecules with regular molecular structure are easily pulled out of the crystallization area and gradually transferred to the coating surface, forming a 20-30nm thick film on the friction surface by Coulomb force and van der Waals force. The macromolecules of this film are highly oriented in the sliding direction, so the friction coefficient is very low, which plays a role of self-lubrication and improves the wear resistance, hardness and scratch resistance of the wear-resistant layer within a certain range.

[0020] Nano-alumina and polytetrafluoroethylene wax cooperate with each other to disperse the nano-alumina in the wear-resistant layer, and under the lubrication of polytetrafluoroethylene wax, the nano-alumina can be dispersed on the surface of the wear-resistant layer, that is, wear occurs preferentially at the nano-alumina, further improving the wear resistance of the wear-resistant layer.

[0021] Optionally, the mass ratio of the nano-alumina to the polytetrafluoroethylene wax is 10-11:10.

[0022] By adopting the above technical scheme, the wear-resistant layer can obtain excellent strength and self-lubricating effect under suitable ratio, and the polytetrafluoroethylene wax can fully lubricate and wrap the nano-aluminum oxide, which is beneficial for the wear-resistant layer to obtain excellent wear-resistant effect.

[0023] Optionally, the wear-resistant filler further includes silica aerogel and chopped flax fibers.

[0024] By adopting the above technical scheme, it is preferred to add silica aerogel and short-cut flax fibers to the wear-resistant filler. The silica aerogel has a multi-space structure, and the short-cut flax fibers can cooperate with the silica aerogel to form a linear-particle composite structure, which can form an interwoven network structure in the wear-resistant layer. The silica aerogel can float on the surface of the wear-resistant layer due to its lighter weight, and when the tear-resistant tent cloth is subjected to impact, the silica aerogel is impacted in advance, and the short-cut flax fibers disperse the impact, thereby further improving the impact resistance and tear resistance of the wear-resistant layer.

[0025] Optionally, the silica aerogel is prepared as follows: MTMS, TEOS, deionized water, ethanol and 1% HCl by mass are mixed and stirred in a container, and then 1 mL of propylene oxide is added dropwise, the pH value is adjusted to about 6, and stirring is continued for 10 minutes to form a silica sol. After gelation, ethanol is added and aged in a 50°C oven for 1 day. After solvent replacement with ethanol solutions of 50% and 100% n-hexane by volume for 24 hours, the wet gel is placed in an oven and dried step by step, first at 50°C for 1 day, and then at 85 and 120°C for 2 and 1 hour, respectively, to finally obtain a silica aerogel.

[0026] Optionally, the chopped flax fibers are chopped flax fibers treated with NaOH-silane.

[0027] By adopting the above technical scheme, the short flax fibers are modified by using NaOH-silane, so that a dispersed fiber structure can be formed on the short flax fibers, that is, a structure similar to branches growing on the surface of the short flax fibers, thereby improving the bonding effect between the short flax fibers and the wear-resistant layer, that is, the short flax fibers can be stably placed in the wear-resistant layer to achieve an impact-resistant effect.

[0028] In summary, this application has the following beneficial effects:

[0029] 1. In the technical solution of this application, ultra-high molecular weight polyethylene, cationic modified polyester and flame-retardant acrylic are preferably used as the base fabric layer. Ultra-high molecular weight polyethylene fiber is a high-performance fiber recognized in the world today, with the advantages of light weight, high strength, high modulus, light resistance, friction resistance, cutting resistance, flex resistance, acid and alkali resistance, and resistance to general organic solvents. The base fabric prepared from ultra-high molecular weight polyethylene staple fiber / cationic modified polyester / flame-retardant acrylic fiber is light in weight, easy to carry, and has extremely high tear strength. It also has the functions of waterproof and breathable, flame retardant, UV protection, mildew resistance, aging resistance, and chemical corrosion resistance. The unique puncture and cut resistance of ultra-high molecular weight polyethylene fiber can be fully utilized, thereby effectively improving the easy tearing effect of the tent fabric.

[0030] 2. In the present application, nano-alumina is preferably used as a hard aggregate to fill the wear-resistant layer, forming a supporting skeleton in the wear-resistant layer, which is beneficial to improve the hardness and strength of the wear-resistant layer, and makes the wear-resistant filler protrude during the friction process, further protecting the wear-resistant layer, especially after the initial stage of wear, the filler particles protrude more and more, and the wear occurs selectively on the surface of the filler, and the wear of the entire wear-resistant layer is stable.

[0031] 3. The present application adopts the method of adding silica aerogel and chopped flax fibers to the wear-resistant filler. The silica aerogel has a multi-space structure, and the chopped flax fibers can cooperate with the silica aerogel to form a linear-particle composite structure, which can form an interwoven network structure in the wear-resistant layer. The silica aerogel can float on the surface of the wear-resistant layer due to its lighter weight. When the tear-resistant tent cloth is subjected to impact, the silica aerogel is impacted in advance, and the chopped flax fibers disperse the impact, thereby further improving the impact resistance and tear resistance of the wear-resistant layer.

[0032] 4. The present application utilizes NaOH-silane to modify the chopped flax fibers, so that a dispersed fiber structure can be formed on the chopped flax fibers, that is, a structure similar to branches growing on the surface of the chopped flax fibers, thereby improving the bonding effect between the chopped flax fibers and the wear-resistant layer, that is, the chopped flax fibers can be stably present in the wear-resistant layer to achieve an impact-resistant effect. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] Preparation Example

[0035] Base fabric preparation example

[0036] Preparation Example 1

[0037] The density is 0.964g / cm 2 Ultra-high molecular weight polyethylene, cationic modified polyester and flame-retardant acrylic fiber are blended in a mass ratio of 70:20:10 to form yarn, which is then woven to prepare a base fabric.

[0038] Silica Aerogel Preparation Example

[0039] Preparation Example 2

[0040] MTMS, TEOS, deionized water (2 mL), ethanol (9.6 mL) and 1% HCl (0.48 mL) (the molar ratio of MTMS / TEOS / EtOH / H2O is 0.5:0.5:9:6) are mixed and stirred in a beaker. After stirring for 23 h, 1 mL of propylene oxide is added dropwise, the pH value is adjusted to about 6, and stirring is continued for 10 min to form a silica sol. The prepared sol is poured into a 50 mL beaker and waited for gelation at 50 ° C. After gelation, ethanol is added and aged in a 50 ° C oven for 1 day. After solvent replacement with ethanol solutions of 50% and 100% n-hexane by volume for 24 h, the wet gel is placed in an oven and dried step by step, first at 50 ° C for 1 day, and then at 85 and 120 ° C for 2 and 1 h, respectively, to finally obtain silica aerogel.

[0041] Preparation Example 3

[0042] Silica aerogel and short chopped flax fibers were taken in a mass ratio of 2:1, dispersed in anhydrous ethanol, 1% carboxymethyl cellulose was added, stirred and dispersed, filtered, and dried to prepare a silica aerogel-flax fiber composite material.

[0043] Preparation Example 4

[0044] The flax fiber was immersed in a 4% sodium hydroxide solution for 30 minutes, taken out, neutralized with a 5% acetic acid solution, thoroughly washed with distilled water, and dried at 70°C for 24 hours. A 30wt.% ethanol aqueous solution was prepared, and then the silane solution was dissolved in the ethanol aqueous solution to make the silane concentration 2wt.%. After the flax fiber was immersed in the silane solution at room temperature for 3 hours, the fiber was taken out and placed in the air for 24 hours, and then the fiber was dried at 70°C for 20 hours to obtain a surface-treated flax fiber.

[0045] Silica aerogel and surface-treated flax fiber were taken in a mass ratio of 2:1, dispersed in anhydrous ethanol, 1% carboxymethyl cellulose was added, stirred and dispersed, filtered, and dried to prepare a silica aerogel-flax fiber composite material.

[0046] Preparation example of wear-resistant filler

[0047] Preparation Example 5

[0048] Polytetrafluoroethylene wax and nano-alumina are taken in a mass ratio of 10:10 respectively, stirred and mixed to obtain a wear-resistant filler.

[0049] Preparation Example 6

[0050] Polytetrafluoroethylene wax and nano-alumina are taken in a mass ratio of 10:11 respectively, stirred and mixed to obtain a wear-resistant filler.

[0051] Preparation Example 7

[0052] Polytetrafluoroethylene wax, nano-alumina and the silica aerogel-flax fiber composite material prepared in Preparation Example 3 were taken in a mass ratio of 10:11:5, stirred and mixed to obtain a wear-resistant filler.

[0053] Preparation Example 8

[0054] Polytetrafluoroethylene wax, nano-alumina and the silica aerogel-flax fiber composite material prepared in Preparation Example 4 were taken in a mass ratio of 10:11:5, stirred and mixed to obtain a wear-resistant filler.

[0055] Example

[0056] Examples 1-3

[0057] The present application provides a method for preparing a tear-resistant tent fabric. 1. The tent fabric comprises a base fabric layer and a waterproof layer and a wear-resistant layer sequentially arranged on the surface of the base fabric layer, wherein the base fabric layer is made of ultra-high molecular weight polyethylene, cationically modified polyester and flame-retardant acrylic fiber; the wear-resistant layer comprises the following raw materials: polyurethane emulsion; wear-resistant filler; wetting agent; defoaming agent; thickener; leveling agent, and the specific quality is shown in the table below.

[0058] Among them, the base fabric layer is the base fabric prepared in Preparation Example 1, the wetting agent, defoamer, thickener, leveling agent and polyurethane emulsion are all commercially available products, the waterproof layer is prepared by coating a commercially available waterproof coating, the wear-resistant layer is prepared by coating a wear-resistant coating, and the wear-resistant filler is the wear-resistant filler prepared in Preparation Example 5.

[0059] Table 1 Composition of wear-resistant coatings in Examples 1-3

[0060] Weight / kg Example 1 Example 2 Example 3 Polyurethane emulsion 30 35 40 Wear-resistant filler 5 8 10 Wetting agent 0.3 0.5 1 Defoaming agent 0.2 0.5 0.8 Thickener 0.5 1 2 Leveling agent 0.1 0.3 0.5

[0061] Example 4

[0062] The difference from Example 2 is that the wear-resistant filler prepared in Preparation Example 6 of equal mass is used to replace the wear-resistant filler in Example 2 to prepare the tent fabric.

[0063] Example 5

[0064] The difference from Example 2 is that the wear-resistant filler prepared in Preparation Example 7 of equal mass is used to replace the wear-resistant filler in Example 2 to prepare the tent fabric.

[0065] Example 6

[0066] The difference from Example 2 is that the wear-resistant filler prepared in Preparation Example 8 of equal mass is used to replace the wear-resistant filler in Example 2 to prepare the tent fabric.

[0067] Comparative Example

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 2 is that the base fabric in this comparative example is prepared from blended yarn of cotton fiber, cationic modified polyester and flame retardant acrylic fiber in a mass ratio of 70:20:10.

[0070] Comparative Example 2

[0071] The difference between this comparative example and Example 3 is that no polytetrafluoroethylene wax is added to the wear-resistant filler in this comparative example.

[0072] Performance testing

[0073] (1) Tear resistance test: Test the tear resistance of tent fabrics according to GB / T3917.1-2009;

[0074] (2) Wear resistance test: The wear resistance of the wear-resistant layer was determined using a grinder in accordance with ASTM D4060-2019.

[0075] (3) Impact resistance test: Test the impact resistance of the wear-resistant layer according to GB / T 13448-2019.

[0076] Table 3 Performance test table

[0077]

[0078]

[0079] By referring to the performance test comparison in Table 3, we can find that:

[0080] 1. Combining Examples 1-3 and Comparative Examples 1-2, it can be found that the tear resistance and wear resistance of the tent fabric prepared in Examples 1-3 are improved, which shows that the base fabric prepared by ultra-high molecular weight polyethylene staple fiber / cationic modified polyester / flame-retardant acrylic fiber in this application is light in weight, easy to carry, and has extremely high tear strength. It also has the functions of waterproof and breathable, flame retardant, UV-proof, mildew-proof, aging-resistant, and chemical-resistant. The unique puncture-proof and cut-proof properties of ultra-high molecular weight polyethylene fibers can be fully utilized, thereby effectively improving the easy-tear effect of the tent fabric. Polyurethane emulsion and wear-resistant filler are combined to form a wear-resistant coating. Polyurethane emulsion itself has good mechanical properties, wear resistance and oil resistance. The introduction of wear-resistant fillers can further increase the wear resistance and mechanical strength of the wear-resistant coating, so that the tent fabric has excellent wear resistance and service life.

[0081] 2. By comparing Example 4 with Example 2, it can be found that the tear resistance and wear resistance of the tent fabric prepared in Example 4 are improved, which indicates that in the present application, nano-alumina and polytetrafluoroethylene wax cooperate with each other to disperse the nano-alumina in the wear-resistant layer, and under the lubrication of polytetrafluoroethylene wax, the nano-alumina can be dispersed on the surface of the wear-resistant layer, that is, wear occurs preferentially at the nano-alumina, further improving the wear resistance of the wear-resistant layer. Since nano-alumina is filled in the wear-resistant layer as a hard aggregate and forms a supporting skeleton in the wear-resistant layer, it is beneficial to improve the hardness and strength of the wear-resistant layer. Therefore, after optimizing the mass ratio of each component in the wear-resistant filler, it can be beneficial to improve the wear resistance of the tent fabric.

[0082] 3. By comparing Example 5 with Example 2, it can be found that the tear resistance, wear resistance and impact resistance of the tent fabric prepared in Example 5 are improved, which means that the silica aerogel in the present application has a multi-space structure, and the chopped flax fibers can be combined with the silica aerogel to form a linear-particle composite structure, which can form an interwoven network structure in the wear-resistant layer. The silica aerogel can float on the surface of the wear-resistant layer due to its lighter weight, and when the tear-resistant tent cloth is subjected to impact, the silica aerogel is impacted in advance, and the chopped flax fibers disperse the impact, thereby further improving the impact resistance and tear resistance of the wear-resistant layer.

[0083] 4. By comparing Example 6 with Example 2, it can be found that the tear resistance, wear resistance and impact resistance of the tent fabric prepared in Example 6 are improved, which means that the modification of the chopped flax fibers using NaOH-silane in the present application can form a dispersed fiber structure on the chopped flax fibers, that is, a structure similar to branches growing on the surface of the chopped flax fibers, thereby improving the bonding effect between the chopped flax fibers and the wear-resistant layer, that is, the chopped flax fibers can be stably present in the wear-resistant layer to achieve an impact-resistant effect.

[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing tear-resistant tent fabric, characterized in that: The tent fabric comprises a base fabric layer, a waterproof layer and a wear-resistant layer sequentially arranged on the surface of the base fabric layer, wherein the base fabric layer is made of ultra-high molecular weight polyethylene, cationic modified polyester and flame-retardant acrylic fiber; the wear-resistant layer comprises the following raw materials in parts by weight: 30-40 parts of polyurethane emulsion; 5-10 parts of wear-resistant filler; Wetting agent 0.3-1 part; Defoaming agent 0.2-0.8 parts; Thickener 0.5-2 parts; 0.1-0.5 parts of leveling agent.

2. The method for preparing a tear-resistant tent fabric according to claim 1, characterized in that: The mass ratio of the ultra-high molecular weight polyethylene, the cationic modified polyester and the flame-retardant acrylic fiber is 60-70:20-30:10-20.

3. The method for preparing a tear-resistant tent fabric according to claim 1, characterized in that: The density of the ultra-high molecular weight polyethylene is 0.920-0.964 g / cm 2 .

4. The method for preparing a tear-resistant tent fabric according to claim 1, characterized in that: The wear-resistant filler comprises nano-aluminum oxide and polytetrafluoroethylene wax.

5. The method for preparing a tear-resistant tent fabric according to claim 3, characterized in that: The mass ratio of the nano-alumina to the polytetrafluoroethylene wax is 10-11:

10.

6. The method for preparing a tear-resistant tent fabric according to claim 4, characterized in that: The wear-resistant filler also includes silica aerogel and short-cut flax fibers.

7. The method for preparing a tear-resistant tent fabric according to claim 6, characterized in that: The silica aerogel is prepared as follows: MTMS, TEOS, deionized water, ethanol and 1% HCl by mass are mixed and stirred in a container, then 1 mL of propylene oxide is added dropwise, the pH value is adjusted to about 6, and stirring is continued for 10 minutes to form a silica sol. After gelation, ethanol is added and aged in a 50° C. oven for 1 day. After solvent replacement with ethanol solutions of n-hexane with volume fractions of 50% and 100% for 24 hours, the wet gel is placed in an oven and dried step by step, first at 50° C. for 1 day, and then at 85 and 120° C. for 2 and 1 hour, respectively, to finally obtain a silica aerogel.

8. The method for preparing a tear-resistant tent fabric according to claim 6, characterized in that: The chopped flax fibers are chopped flax fibers treated with NaOH-silane.